Digital Fiqh and Maqāṣid al-Sharīʿah in the Onlife Condition: A Digital Hermeneutic Critique of Algorithmic Power for Islamic Pistemic Sovereignty - Ja'far, Suhermanto; Yaqin, Haqqul; Iffah, Iffah; Hodri, Hodri; Sanuri, Sanuri (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the growing influence of algorithmic governance on religious authority and knowledge production in digital environments, particularly within the Muslim digital sphere. In the contemporary onlife condition, where online and offline realities increasingly converge, algorithmic systems shape the visibility, interpretation, and circulation of Islamic discourse. This raises a critical question: how can Islamic jurisprudence respond to the epistemic and ethical challenges posed by algorithmic power? This article explores digital fiqh as an epistemological and normative framework capable of critically engaging algorithmic structures through the lens of maqāṣid al-sharīʿah. The study employs a critical qualitative approach using digital hermeneutics and multidisciplinary literature analysis, drawing on theoretical perspectives from algorithmic epistemology, Islamic legal theory, and digital ethics. The findings indicate that fiqh should be reinterpreted not merely as a legal product but as an epistemic apparatus capable of evaluating algorithmic governance and negotiating justice, dignity, and meaning in digitally mediated environments. Theoretically, this study expands the scope of maqāṣid into the domain of digital ethics, addressing issues such as privacy, algorithmic bias, and data commodification. Practically, it proposes the integration of digital literacy in Islamic education, the development of alternative digital platforms, and the promotion of digital self-determination within Muslim communities. This article argues that digital fiqh can function not only as a normative response to technological change but also as a decolonial strategy for reclaiming Islamic epistemic sovereignty in the algorithmic world order.